2004
DOI: 10.1097/01.ta.0000096644.08735.72
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Head and Extracranial Injuries on Serum Protein S100B Levels in Trauma Patients

Abstract: We conclude that serum S100B is a sensitive marker of brain injury, which correlates with the severity of the injury. Large extracranial injuries also elevate S100B levels. However, S100B has a high negative predictive power, and the finding of a normal S100B value shortly after trauma should thus exclude significant brain injury with a high accuracy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
144
0
8

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 206 publications
(161 citation statements)
references
References 20 publications
9
144
0
8
Order By: Relevance
“…The initial S100 levels in patients with TBI (CCTq) were even slightly lower than those without TBI (CCT-). These biochemical observations have already been reported by other authors, who mostly used the Sangtec ᮋ 100 immunoassay on a LIA-mat ᮋ S100 analyzer (35,36). Extracerebral sources of S100 release into the systemic circulation obviously seem to play an important role in multiple trauma patients.…”
Section: Bereitgestellt Von | Universitaetsbibliothek Der Lmu Muenchensupporting
confidence: 55%
“…The initial S100 levels in patients with TBI (CCTq) were even slightly lower than those without TBI (CCT-). These biochemical observations have already been reported by other authors, who mostly used the Sangtec ᮋ 100 immunoassay on a LIA-mat ᮋ S100 analyzer (35,36). Extracerebral sources of S100 release into the systemic circulation obviously seem to play an important role in multiple trauma patients.…”
Section: Bereitgestellt Von | Universitaetsbibliothek Der Lmu Muenchensupporting
confidence: 55%
“…This has raised concerns as to whether the serum levels of this protein actually correlate with the degree of brain damage or are more reflective of blood brain barrier (BBB) disruption. Secondly, S100B has been reported to be released into the serum after experimental ischemic injury to the liver, kidney, and gut; 16 its levels have been found to have increased after extracranial trauma 14 and burns, 17 and it has been suggested to be a biomarker of melanoma. 18 Finally, conflicting reports have been published regarding the usefulness of this marker in predicting outcome after pediatric TBI.…”
Section: S100bmentioning
confidence: 99%
“…Similar to that observed at higher injury magnitudes, the serum concentration of this marker is transiently increased after MTBI. 14 For example, a clinical study evaluating serum S100B levels in patients with mild head injuries found that patients with intracranial injuries (as determined by using head CT scans) had significant elevations in S100B levels compared with patients who did not have such injuries. 95 Consistent with this evaluation, a recent re-evaluation of six prospective clinical trials involving more than 2000 MTBI patients indicated that S100B has a sensitivity of 98.2% in identifying the presence of brain injury.…”
Section: Biomarkers For Mild Tbimentioning
confidence: 99%
“…It has been shown that injury other than head trauma can be the cause of increased S-100β levels. 23 Anderson and colleagues have demonstrated that S-100β levels can be increased up to 40 times as a consequence of soft tissue trauma and increased by two orders of magnitude after bone fractures. 24 In order to exclude extracranial injury as confounding factor in our study, we excluded 49 of the originally recruited patients because of significant additional trauma other than head injury, most commonly fractures of the extremities (n =14), serial rib fractures (n = 11) and pneumothorax (n = 6).…”
Section: Methodsmentioning
confidence: 99%